Comparative Analysis of Energy Storage Technologies for Microgrids - Mohamed Haikel Chehab; Chokri Ben Salah; Ruben Zieba Falama; Mehdi Tlija; Abdelhamid Rabhi (International Transactions on Electrical Energy Systems)
Nowadays, microgrids (MGs) are receiving a lot of attention. In an economical MG, the battery energy storage system (BESS) plays an important role. One of the biggest challenges in MGs is the optimal choice of the BESS that can lead to better performance of the MG, which will be more flexible, efficient, and effective than traditional power systems. In this paper, we present the modeling and simulation of different energy storage systems including Li-ion, lead-acid, nickel cadmium (Ni-Cd), nickel-metal hybrid (Ni-Mh), and supercapacitor (SC), for renewable energy applications, and more specifically for MGs. The results of simulation show that Li-ion batteries have a better response time than lead-acid batteries, Ni-Cd batteries, and Ni-Mh batteries and thus are more suitable for combination with supercapacitors. Li-ion batteries are the best option for fast-charging applications in MGs. The discharge phase ends with SOC ≤ ±94%, SOC ≤ ±95%, SOC = 95%, SOC < 95%, and SOC < 60%, respectively, for Li-ion, lead-acid, Ni-Cd, Ni-Mh, and supercapacitor. Moreover, the use of the battery management system (BMS) can significantly improve the performance of BESS, leading to higher levels of SOC and longer life span. The obtained results have shown that with an optimization algorithm for energy storage systems, more specifically for the battery-charging mode, the response time of BESSs can be further improved. The effect of ambient temperature has also been investigated on the functional capacities of the batteries. The obtained results demonstrated that extreme temperatures (80°C to −80°C) have a significant impact on battery performance and capacity, especially for Li-ion batteries, with a drop in capacity of up to 50% at −40°C. This highlights the importance of considering the ambient temperature in the design and operation of MGs. Overall, our study provides valuable insights into the optimal selection of BESS and the impact of ambient temperature on their performance, which can help in the development of more efficient and reliable MGs.